Toxicity of the Colicin M Catalytic Domain Exported to the Periplasm Is FkpA Independent - Barnéoud-Arnoulet, Aurélie (American Society for Microbiology (ASM), 2010)
Colicin M (ColM) is a bactericidal protein that kills sensitive cells by hydrolyzing lipid II, involved in the biosynthesis of cell wall peptidoglycan. It recognizes FhuA on the outer leaflet, and its translocation through the outer membrane depends on the energized Ton complex in the inner membrane. To be active in the periplasm, ColM must be translocated through the outer membrane and then interact with FkpA, a periplasmic protein that exhibits both cis- and trans-peptidylprolyl isomerase (PPiase) and chaperon activities. In an attempt to directly target ColM to the periplasm of the producing bacteria, we fused the presequence of OmpA to ColM (sp-ColM). We found that expression of this hybrid protein in an Escherichia coli strain devoid of ColM immunity protein (Cmi) was bactericidal. We showed that sp-ColM was correctly expressed, processed, and associated with the inner membrane. sp-ColM toxicity was related to its enzymatic activity and did not rely on the TonB import proteins or the FhuA receptor. The presence of both activity domains of FkpA was still required for sp-ColM activity. Analyses of deletion mutants of sp-ColM show that the domain required for toxicity corresponds to the C-terminal last 153 amino acids of ColM. Like the full-length protein, this domain is not active in the presence of the immunity protein Cmi. On the other hand, it does not require FkpA for toxic activity.